Implementation Authority Of The Constitutional Court In The Indonesian Constitutional Law System - Thohir, Moh.; Sukriono, Didik (International Journal of Business, Law, and Education, 2023)
This study explores the evolution and significance of the Constitutional Court in Indonesia, examining its speculated super authority and unilateral interpretation of the Constitution. The research delves into the court's exclusive jurisdiction, rendering its decisions final and binding, thereby limiting legal recourse for dissatisfied parties. Grounded in the global development of judicial review, notably the landmark Marbury versus Madison case by John Marshall, the Constitutional Court's role is integral to constitutional interpretation. Originating from discussions during the Draft Constitution at BPUPKI and resurfacing during deliberations on the Draft Law on Judicial Power (UU Number 14 of 1970), the importance of the Constitutional Court gained prominence during the 1945 reform era. The Third Amendment to the 1945 Constitution solidified the court's establishment as a guardian of the constitution, shaping its pivotal role in constitutional interpretation in Indonesia. This research aims to provide a comprehensive understanding of the Constitutional Court's journey, its unique authority, and its crucial role in the country's legal and constitutional landscape